Sugar and spice - Mlynowski, Sarah (Mlynowski, Sarah. Whatever after, 2016)
In this trip through the magic mirror, Abby and Jonah find themselves in the tale of Hansel and Gretel, where they have to deal with the witch and hope the portal will open so they can get home.